Startup CEO : a field guide to scaling up your business - Blumberg, Matt.; Hindi, Hanny (Hoboken, N.J. : Wiley, 2013)
A definitive book for any CEO-first time or otherwise-of a high-growth company While big company CEOs are usually groomed for the job for years, startup CEOs aren't-and they're often young and relatively inexperienced in business in general. Author Matt Blumberg, a technology and marketing entrepreneur, knows this all too well. Back in 1999, he started a company called Return Path, which later became the driving force behind the creation of his blog, OnlyOnce-because ""you're only a first time CEO once."" Now, more than a decade later, he's written Startup CEO. As the fif
pt. 1. Storytelling -- pt. 2. Building the company's human capital -- pt. 3. Execution -- pt. 4. Building and leading a board of directors -- pt. 5. Managing yourself so you can manage others.
Includes bibliographical references and index.
English.
John Wiley and Sons
Keywords: New business enterprises -- Management; Nouvelles entreprises -- Gestion; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Chief executive officers; Corporate governance; New business enterprises -- Management; Small business -- Management; New business enterprises -- Management